Dalang Topeng dalam Upacara Ngarot: Representasi Sejarah Lokal dan Identitas Budaya Masyarakat Indramayu - isad suhaeb; Asti Kurniawati; Eva Farhat (PANGGUNG, 2026)
This study examines the role of the topeng (mask) puppeteer in the Ngarot traditional ceremony in Lelea, Indramayu, as a representation of local history and cultural identity of the coastal Javanese community. The Ngarot tradition, rooted in agrarian history, is combined with mask performance, creating a space of expression that reflects social, religious, and historical values. The topeng puppeteer functions not only as a performer but also as a guardian of historical narratives transmitted orally through symbols, movements, and performance dialogues. Using an ethnographic approach, this research explores the dynamics of the puppeteer’s role and the meanings constructed within the ceremonial context. The findings show that the topeng puppeteer acts as a cultural agent who affirms collective identity while strengthening the educational function of history through performing arts. Thus, Ngarot and Indramayu mask traditions can be understood as living cultural heritage that remains relevant to community life.